A clinician's perspective of the role of renal sympathetic nerves in hypertension - Briasoulis, Alexandros; Bakris, George L. (Frontiers in Physiology, 2015)
The renal sympathetic nerves have a significant contribution to the control of different aspects of kidney function and blood pressure. Early animal studies of renal denervation (RDN) in a large number of different models of hypertension showed that RDN improved blood pressure (BP) control. Recently, data from prospective cohorts and randomized studies showed that RDN is a safe procedure but is associated with only modest reduction of ambulatory BP in patients on multiple antihypertensive medications. The main goal of this article is to review the results of preclinical and clinical studies that focus on the contribution of the renal sympathetic nervous system to development and maintenance of hypertension. It also reviews the therapeutic applications and evolution of catheter-based renal denervation.